Developing Digital Pop-Up Book media to enhance Fine Arts learning in primary education - Primadianti, Rosita Kurnia; Nurharini , Atip (Journal of Educational Management and Instruction (JEMIN), 2025)
The lack of engaging learning media in elementary education can hinder students’ learning skills and reduce their motivation. This study aims to develop, assess the feasibility, and evaluate the effectiveness of digital pop-up book media to enhance student learning outcomes in Fine Arts Education. This study employed a development model adapted from Borg & Gall, simplified into eight stages: identifying problems and potentials, data collection, media design, design validation, design revision, initial trial, product revision, and implementation trial. The participants included one media expert, one material expert, a teacher, and 21 Grade I elementary school students. Data were collected through observation, interviews, documentation, questionnaires, and tests, using instruments such as validation forms and pretest-posttest questions. Analysis methods included qualitative descriptive analysis, as well as quantitative and inferential statistics. The validation results from media and material experts showed very high feasibility, with percentage scores of 88.33% and 91.67% respectively. Teacher and student responses indicated high interest and positive reception toward the digital media. Furthermore, the results of the paired t-test revealed a statistically significant improvement in student learning outcomes after using the media. These findings suggest that digital pop-up book media is not only feasible and engaging but also effective in improving students’ fine motor and cognitive skills in Fine Arts Education. This media holds potential as a valuable tool for enhancing primary school instruction through interactive and technology-integrated learning.